Paweł Jasienica - an Intellectual Sketch - Kierys, Arkadiusz (Sensus Historiae, 2019)
Paweł Jasienica belonged to a generation of Polish intellectuals who had not spent one day of their adult and creative life in the democratic Poland. First, they went through the autoritharianism of Sanation, then through the war occupation by two totalitarian regimes, and finally through the Moscow-dependent Polish People’s Republic. Still, Jasienica, who was formed by the academic circle of the University of Stefan Batory in Vilnius, was part of a small group of liberals. In his work, both as a journalist and author, he always went against the grain of what was popular. In a supremely Catholic country, he was a fierce opponent of antisemitism and he stood in defence of the Jewish minority. During the occupation, he was against engaging the youth too much in the fighting in the hope that, after the war, it may replace those whose loss the intelligentsia had suffered. He did not commend the underground warfare, thinking that the guerrilla contributes to moral degeneration, without exception. For him, morally ambiguous was also the act of displacing the German minority from the lands given to Poland after the war, as well as destroying the cultural heritage of those regions. Jasienica remains in the Polish collective memory as the historian of the pre-Partitions Poland, the tales of which were contrary to the ideals of official Marxist historiography, and thanks to which he garnered a vast readership, as well as some sworn enemies among those in power. His defence of the students protesting for the freedom of expression in March 1968 is also part of history. Jasienica is one of the greatest Polish authors and intellectuals.